A systematic review of diapoma (teleostei: characiformes: characidae: stevardiinae: diapomini) with descriptions of two new species from southern Brazil - Menezes, Naércio A.; Weitzman, Stanley H. (Papéis Avulsos de Zoologia, 2011)
Diapoma is reviewed and four species are recognized: (1) Diapoma thauma, new species, from streams of the rio Jacuí basin, state of Rio Grande do Sul; (2) D. pyrrhopteryx, new species collected from the rio Canoas and streams flowing into this basin in the states of Rio Grande do Sul and Santa Catarina, Brazil; (3) Diapoma terofali, from streams flowing into rio Uruguay in Uruguay and Rio Grande do Sul, Brazil and streams flowing into rio de la Plata, Argentina; and (4) Diapoma speculiferum, from lowland coastal streams in Rio Grande do Sul, Brazil and Uruguay. Diapoma pyrrhopteryx possess the posteroventral opercular elongation typical of D. speculiferum, type species of the genus, but which is absent in D. thauma and D. terofali. Nonetheless, all the diapomin species have the caudal pouch organ about equally developed in both sexes and the dorsal portion of the pouch opening bordered by a series of 3 to 8 elongated scales, the two derived features that characterize the group. The two previously described species, D. speculiferum and D. terofali, are redescribed. Previous hypotheses of relationships among the diapomin genera Planaltina, Diapoma and Acrobrycon are discussed on the basis of preliminary morphological information. It is proposed that the Diapomini is a monophyletic group. An identification key, information on sexual dimorphism, gonad anatomy, reproductive mode and distribution of the species of Diapoma are provided.